2021
DOI: 10.1155/2021/5527215
|View full text |Cite
|
Sign up to set email alerts
|

Research on Coordination of Fresh Agricultural Product Supply Chain considering Fresh-Keeping Effort Level under Retailer Risk Avoidance

Abstract: Considering that the demand for fresh agricultural products is affected by product freshness and price, a two-level fresh agricultural product supply chain decision model consisting of a risk-neutral supplier and a risk-averse retailer is constructed. In order to increase consumer demand for fresh agricultural products, the supplier will make appropriate efforts to preserve the freshness of agricultural products. The optimal fresh-keeping effort level of the supplier and the optimal pricing decision of the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Sweeney et al (2018) highlighted the importance for supply chain practitioners to compare their own perspectives on supply chain management and logistics relationships with those of their supply chain partners. Feng et al (2021) proposed a coordination mechanism of fresh agricultural product supply chain considering fresh-keeping effort level under retailer risk avoidance, and the research showed that the traditional cost-sharing contract and the traditional cost-benefit sharing contract can achieve supply chain coordination only under some certain conditions. Hu et al (2021) constructed a framework that leveraged blockchain and edge computing to resolve the trust issue of organic agriculture supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Sweeney et al (2018) highlighted the importance for supply chain practitioners to compare their own perspectives on supply chain management and logistics relationships with those of their supply chain partners. Feng et al (2021) proposed a coordination mechanism of fresh agricultural product supply chain considering fresh-keeping effort level under retailer risk avoidance, and the research showed that the traditional cost-sharing contract and the traditional cost-benefit sharing contract can achieve supply chain coordination only under some certain conditions. Hu et al (2021) constructed a framework that leveraged blockchain and edge computing to resolve the trust issue of organic agriculture supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the event of drought and floods, agricultural production will be greatly reduced in a short period of time, and it is difficult to adjust, which can easily lead to fluctuations in agricultural product prices; secondly, our country's agricultural production mainly relies on household production. This market is fragmented, and the market position is low [17]. They cannot obtain timely supply and marketing information and are unable to deal with market risks.…”
Section: Research On the Construction Of Sustainablementioning
confidence: 99%
“…The second area of research is related to the coordination models of short lifetime products SC. In the related literature, different issues such as logistics outsourcing [4], freshness-keeping efforts [3,10,55], cost and loss disruptions [44], and preservation technology investment [28] have been addressed. Furthermore, the risk of unsold products at the end of selling season is studied by some researchers.…”
Section: Literature Reviewmentioning
confidence: 99%